FORMULASI SEDIAAN GEL ANTISEPTIK (HANDSANITIZER) EKSTRAK ETANOL DAUN BABANDOTAN (Ageratum conyzoides Linn.) DENGAN BASIS HPMC TERHADAP AKTIVITAS ANTIBAKTERI Staphylococcus aureus - cory Imawati. imawati (PHRASE (Pharmaceutical Science) Journal, 2022)
The disease is often derived from microorganisms with one of the spread through the hands. Microorganisms are often found in the hands one of them is the bacterium staphylocococus aureus. Ethanol extract of babandotan leaves has been proven to have antibacterial activity to staphylococcus aureus bacteria . The purpose of this research is to develop gel preparation of antiseptic with active ingredient that is ethanol extract from babandotan leaves. The extraction method used was maceration with 70% ethanol solvent. The dosage formulation was prepared with HPMC (Hydroxy propyl methyl cellulose) as a gelling agent with 2% constraction. The concentration of ethanol extract of babandotan leaves used was 80%. Antibacterial testing method used is disc diffusion method. Gel handsanitizer tested its physical properties include viscosity test, organoleptic test, homogeneity test, spreading test and PH. Babandotan leaves ethanol extract with 80% concentration had antibacterial activity obtained by 11 mm inhibition zone and after gel formulation (Handsanitizer) was obtained the average of 8,8 mm inhibition zone. Organoleptic results show a good handsanitizer gel.